A method for plotting the complementary root locus using the root-locus (positive gain) rules - Teixeira, MCM; Assuncao, E.; Machado, ERMD (Institute of Electrical and Electronics Engineers (IEEE), 2004)
The root-locus method is a well-known and commonly used tool in control system analysis and design. It is an important topic in introductory undergraduate engineering control disciplines. Although complementary root locus (plant with negative gain) is not as common as root locus (plant with positive gain) and in many introductory textbooks for control systems is not presented, it has been shown a valuable tool in control system design. This paper shows that complementary root locus can be plotted using only the well-known construction rules to plot root locus. It can offer for the students a better comprehension on this subject. These results present a procedure to avoid problems that appear in root-locus plots for plants with the same number of poles and zeros.
Keywords: complementary root; control systems; gain; root locus; theory of equations; transfer functions